Analisis Kepuasan Pelanggan Restoran Makanan Crispy di Indonesia: Studi Kasus di Dr. Chicken Cimahpar - Aqila Asysyakur (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2023)
This study aims to evaluate the level of customer satisfaction at Dr. Chicken Cimahpar, a crispy or fresh food restaurant in Indonesia. The problem at hand is how to determine the level of customer satisfaction based on the attributes of the product or service they receive. The method used is the Customer Satisfaction Index (CSI), which determines the level of user satisfaction based on the level of performance and the level of importance of the measured product or service features. The sample of this research is consumers who visit and purchase products in the second observation stage and are willing to be respondents for research. The results showed that Dr. Chicken Cimahpar has a customer satisfaction level of 78.59%, which is within the "satisfied" criteria. The most important factors for consumer satisfaction are food served crispy or fresh and accuracy of order presentation. This research provides valuable insight into the level of consumer satisfaction and can be used by Dr. Chicken Cimahpar to improve its products and services.